Study of non-pollution cultivation techniques of organic ecotype of melon crops considering population characteristics - Chen, Gang (Cellular and Molecular Biology, 2022)
Due to the requirement of melon yield, the cultivated seeds are overused with pesticides during the melon planting process, and the population characteristics are not considered, resulting in serious soil pesticide pollution during the melon planting process. Therefore, this study proposes an organic ecological pollution-free cultivation technology of melon considering population characteristics. The population characteristics of melon crops were determined by DNA molecular marker technology. On this basis, the organic ecotype pollution-free matrix of melon crops was formulated, and the bulk density, total porosity and aeration porosity of the matrix were determined. The MNL model method was used to control the spraying amount of melon cultivation, and the light condition of the melon growing environment was determined by the leaf fluorescence of melon crops. There were significant differences in plant height, stem diameter and leaf area between melons grown in the studied substrate and common soil. With the change of planting days, the height of the melon grown in this technology was always higher than that of the melon grown in common soil, and the maximum value was about 20 cm. As planting days changed, the stem thickness of melon crops grown with the substrate was initially lower than that of common soil, but quickly exceeded the thickness of common soil over time. The surface areas of the third and fourth leaves of the melon crops grown according to this technology varied with the days of planting. Early differences between the two substrates were not significant. However, in later stages, melons grow faster. In the early stage of melon production, the chlorophyll content of pollution-free cultivation was higher than that of common cultivation methods. The flowering period was the period with the highest chlorophyll content in both cultivation techniques. However, the highest content of melon chlorophyll under this technology was about 2.0 mg, and the highest content of melon chlorophyll under common cultivation technology was about 1.4 mg, which verifies the effectiveness of the method. It has been verified that pollution-free cultivation technology can effectively improve the growth efficiency of melon crops and ensure the quality of melon cultivation.